Change in incidence and aetiology of intracerebral haemorrhage in Oxfordshire, UK, between 1981 and 2006: a population-based study. - Lovelock, C; Molyneux, A; Rothwell, P (2007)
BACKGROUND: UK stroke mortality data suggest that the incidence of haemorrhagic stroke has fallen in the past 20 years, but these data do not include deaths of individuals aged 75 years or over. Trends in the older population might differ, since cause varies with age. Our aim was to investigate changes in the population-based incidence of intracerebral haemorrhage according to age and likely aetiology. METHODS: We used data from the Oxford Community Stroke Project (OCSP; 1981-86) and the Oxford Vascular Study (OXVASC; 2002-06) to investigate changes in the incidence of intracerebral haemorrhage with time, above and below age 75 years, together with associated risk factors and premorbid medications. Incidences were standardised to the 2001 census population of England and Wales. FINDINGS: In the population aged under 75 years the incidence of intracerebral haemorrhage decreased substantially (rate ratio 0.53, 95% CI 0.29-0.95; p=0.03), but the number of cases of intracerebral haemorrhage at all ages were similar in OXVASC and OCSP (52 vs 55 cases) as the proportion of cases occurring at 75 years and over tended to increase (2.0, 0.8-4.6; p=0.09). The incidence of intracerebral haemorrhage associated with premorbid hypertension (blood pressure >or=160/100 mm Hg) fell overall (0.37, 0.20-0.69; p=0.002), but the incidence of intracerebral haemorrhage associated with antithrombotic use was increased (7.4, 1.7-32; p=0.007). Above age 75 years the proportion of cases who were non-hypertensive with lobar bleeds and presumed to have had mainly amyloid-related haemorrhages, also increased (4.0, 1.1-17; p=0.003). INTERPRETATION: There has been a substantial fall in hypertension-associated intracerebral haemorrhage over the past 25 years, but not in the overall number of cases of intracerebral haemorrhage in older age-groups, in part due to a rise in intracerebral haemorrhage associated with antithrombotic use. These trends, along with the expected increase in prevalence of amyloid angiopathy with the ageing population, suggest that, in contrast to projections based on mortality data below age 75 years, absolute number of cases of intracerebral haemorrhage might increase in future.